Space and time in languages and cultures - Filipovic', Luna (John Benjamins Pub. Co, 2012)
This item purchased with funds from: the James Fleming Rutledge Book Endowment Fund; Includes bibliographical references and indexes; The topic of space and time in language and culture is also represented, from a different point of view, in the sister volume Space and Time in Languages and Cultures: Language, culture, and cognition (HCP 37) which discusses spatial and temporal constructs in human language, cognition, and culture in order to come closer to a better understanding of the interaction between shared and individual characteristics of language and culture that shape the way people interact with each other and exchange information about the spatio-temporal constructs that underlie their cognitive, social, and linguistic foundations